2022
DOI: 10.3390/ijerph19159058
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Learning Strategies for Nursing Students: A Pilot Randomized Controlled Trial

Abstract: Distance learning (DL) based on information and communication technologies is gaining importance due to its convenience and cost savings. However, there is not enough evidence to identify the effect of DL on students requiring a high level of self-regulated learning (SRL). Therefore, this study aims to compare the effects of the use of augmented reality (AR) as an innovative learning method and the use of a textbook as a conventional learning method. Both methods were based on SRL strategies. In this pilot ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
7
0
5
Order By: Relevance
“…The results of our study showed that students used various self-centered strategies to facilitate their e-learning. In fact, due to the teacher’s physical absence in the e-learning environment, students have more independence in the learning process, and in order to be able to learn and succeed in this type of education, it is necessary to have self-regulation learning skills [ 13 ]. In fact, studies related to e-learning have also found a positive relationship between self-directed learning strategies, academic success, and the e-learning acceptance [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study showed that students used various self-centered strategies to facilitate their e-learning. In fact, due to the teacher’s physical absence in the e-learning environment, students have more independence in the learning process, and in order to be able to learn and succeed in this type of education, it is necessary to have self-regulation learning skills [ 13 ]. In fact, studies related to e-learning have also found a positive relationship between self-directed learning strategies, academic success, and the e-learning acceptance [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…How nursing staff can improve their PI knowledge and enhance the quality of care through effective learning methods without affecting their personal time is currently an important issue in clinical nursing [ 29 ]. E-book apps allow them to self-regulate their learning, manage their time, seek assistance, and perform self-evaluations [ 30 ]. Innovative education strategies offer a promising alternative for PI prevention and care for nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study showed that students used various self-centered strategies to facilitate their elearning. In fact, due to the teacher's physical absence in e-learning environment, students have more independence in the learning process, and in order to be able to learn and succeed in this type of education, it is necessary to have self-regulation learning skills (15). One of the self-centered strategies used by some students was exploration.…”
Section: Self-directed Learning Strategiesmentioning
confidence: 99%